Pathogenesis of Acute Kidney Injury in Coronavirus Disease 2019 - Qian, Jing-Yi; Wang, Bin; Lv, Lin-Li; Liu, Bi-Cheng (Frontiers in Physiology, 2021)
Since the outbreak of Coronavirus Disease 2019 (COVID-19) in Wuhan, China in December of 2019, it has rapidly become a global pandemic. Although acute respiratory disorder is the main manifestation of COVID-19, acute kidney injury (AKI), on the other hand, is also one of the important extrapulmonary involved organ damage, which has critical impact on the prognosis and mortality of patients. Current understanding about the exact pathogenesis of AKI in COVID-19 is largely unclear. Several studies suggested that direct virus attack, overloaded immune responses, sepsis, coagulation dysfunction, drugs, underlying diseases may all be involved in. This article reviews the state of the art understanding of the pathogenesis of AKI in COVID-19.